ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN - Soraya, Elly; Lutfiati, Anis (Kinerja, 2020)
This study is entitled Analysis Of Factors Affecting Financial Literation, Case Study Of As-Syafi’iyah Islamic University, Faculty Of Economics And Business Students, 2020. This study aims to determine the Factors Affecting Student Financial Literacy, these factors include gender, GPA, income of parents and work experience. The population in this study is the active students of the Faculty of Economics and Business of the As-Syafi’iyah Islamic University semester 4 to semester 8, probability sampling techniques, the number of samples used slovin formula. This study uses 232 questionnaires through Google form. The instrument test uses the validity and reliability test. The analytical method used is descriptive statistics, the classic assumption test, the multiple regression test, the multiple correlation coefficient of determination test and the T Test. The test results show that 1). Gender has a positive and significant effect on financial literacy 2). GPA has a positive and significant effect on financial literacy 3). Parents’ income has a positive and significant effect on financial literacy 4). Work Experience has a positive and significant effect on financial literacy. The suggestions from researchers Students can attend various financial literacy seminars, and can utilize social media to follow (follow) various social media accounts of financial institutions or financial consultants and for further researchers can also complement financial literacy variables by looking at their effects on financial attitudes and financial behavior.